Benefits of pentoxifylline for skin flap tissue repair in rats - Pedretti,Stephanie Luzia da Costa (2020)
Abstract Purpose To assess the action of pentoxifylline, administered by subcutaneous route, on skin flap tissue repair in rats, and to verify the histological aspects and biomarkers. Methods Thirty-two male Wistar rats were divided into four groups: control (CT) and treated with pentoxifylline (P1, P3 and P5). Modified McFarlane technique flap was used. Ten days later, the animals were euthanized and the areas of viable and necrotic tissue were evaluated. Hematoxylin/eosin staining was used to assess the morphometric characteristics of the number of vessels and epithelial thickness. Picrosirius red was used to assess collagen density. VEGF and TGF-?1 levels on the skin flap and serum of the animals were measured by the ELISA method. Results The macroscopic evaluation of the skin flap dimensions showed reduced necrotic tissue in the pentoxifylline (p < 0.05) treated groups. There was an increase in angiogenesis and reepithelization, demonstrated by analyses with an increased number of vessels (p < 0.05), VEGF and epithelial thickness. Fibrogenic effect showed decreased collagen density and TGF-β1 in the skin flap and serum. Conclusion The benefits of pentoxifylline administered by subcutaneous route, at dose 100 mg/kg, which was effective to improve the survival of skin flap by acting on tissue repair components, stimulating angiogenesis and reepithelization, in addition to reducing fibrogenesis